1975
DOI: 10.1159/000240757
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Primate Parathyroid Hormone Metabolism

Abstract: Near-term fetal and neonatal parathyroid gland function has been studied in the Rhesus monkey. Fetal serum ionized calcium (Ca++) levels are significantly greater than simultaneously obtained maternal levels. Fetal serum parathyroid hormone (PTH) was undetectable both in the basal state and in association with EDTA-induced fetal hypocalcemia. Induced maternal hypocalcemia was associated with increased maternal serum PTH levels and no change in fetal basal serum Ca++ or PTH levels. Only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Typically the fetal serum calcium is 0.30 -0.50 mM or higher than the maternal level in rhesus monkeys (189,524), lambs (148,201,435,505), calves (201,715), rodents (201,338,340,342,346,347,623), pigs (98,101,353), and foals (201). The ionized calcium is also increased 0.25-0.50 mM above the maternal value in fetal rodents (148,340,422), confirming that true hypercalcemia is present relative to maternal and normal adult values.…”
Section: Animal Datamentioning
confidence: 87%
See 1 more Smart Citation
“…Typically the fetal serum calcium is 0.30 -0.50 mM or higher than the maternal level in rhesus monkeys (189,524), lambs (148,201,435,505), calves (201,715), rodents (201,338,340,342,346,347,623), pigs (98,101,353), and foals (201). The ionized calcium is also increased 0.25-0.50 mM above the maternal value in fetal rodents (148,340,422), confirming that true hypercalcemia is present relative to maternal and normal adult values.…”
Section: Animal Datamentioning
confidence: 87%
“…PTH increases not only with ablation of one or both alleles of Casr (336,340), but in response to EDTA-induced hypocalcemia in fetal lambs (631), calves (715), and rhesus monkeys (524). However, a second study in rhesus monkeys found no increase in fetal PTH in response to EDTAinduced hypocalcemia (189).…”
Section: Pthmentioning
confidence: 97%
“…The effects of EDTA During early human neonatal life, blood sugar regulation is infusions on fetal serum ionized calcium and parathormone levels incompletely developed and hypoglycemia may occur (28). This is were examined during the hour preceding delivery (12). In all particularly frequent in infants from diabetic mothers requiring experiments, serum ionized calcium, plasma glucose levels, exogenous insulin (6,21,22,24,25).…”
Section: Animalsmentioning
confidence: 99%